AGES AND MASSES FOR NINE `SUPERMETALRICH FIELD STARS - TORRES PEIMBERT, S; SPINRAD, H (UNAM, Boletín de Observatorios Tonatzintla y Tacubaya, México., 1971)
A comparison with theoretical evolutionary models was made for nine field K-giants of known supermetallicity and distance, yielding the approximate age and mass of each star. The average values for the group are 6.2*10/sup 9/ years and 1.2 Mo, or 5.5*10/s
BOL OBS TONAN TACUB
Keywords: AGES, MASSES, NINE, SUPER, METAL, RICH, FIELD STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS